2014
DOI: 10.1007/s00264-014-2339-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeted pre-operative autologous blood donation: a prospective study of two thousand and three hundred and fifty total hip arthroplasties

Abstract: Purpose Pre-operative donation of autologous blood has been widely used in elective joint replacement procedures to avoid the risks of allogeneic blood transfusions. However, the high percentage of wasted autologous blood questions the general efficacy of pre-operative autologous blood donation (PABD) for all patients undergoing hip replacement. This study prospectively investigates the impact of a targeted pre-operative autologous blood donation protocol for anaemic patients on allogeneic and overall transfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 15 The most frequently used definition of anemia is the World Health Organization (WHO) 19 classification using a hemoglobin <13 g/dL (men) and <12 g/dL (women). Two SRs, 14 , 20 1 RCT, 21 and several observational studies 22 26 have shown iron (oral and intravenous) supplementation, erythropoietin, and preoperative autologous donation are effective in reducing postoperative allogenic transfusion; however, the benefit on clinical outcomes (ie, LOS and mortality) is unclear. Routine use of these strategies does not appear to benefit nonanemic patients.…”
Section: Resultsmentioning
confidence: 99%
“… 15 The most frequently used definition of anemia is the World Health Organization (WHO) 19 classification using a hemoglobin <13 g/dL (men) and <12 g/dL (women). Two SRs, 14 , 20 1 RCT, 21 and several observational studies 22 26 have shown iron (oral and intravenous) supplementation, erythropoietin, and preoperative autologous donation are effective in reducing postoperative allogenic transfusion; however, the benefit on clinical outcomes (ie, LOS and mortality) is unclear. Routine use of these strategies does not appear to benefit nonanemic patients.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a validated risk score system of allogeneic blood transfusion for lumbar fusion surgery based on retrospective study with large sample size will be implemented to ensure the necessity for PABD programme. Both this technique and EPO injection should be more efficient in the patients with higher risk of blood transfusion 20 24. Waste of donated blood was an inherent risk for PABD programme 25 26.…”
Section: Discussionmentioning
confidence: 99%